Дослідження процесу рафінування твердих сплавів по вуглецю - Бондаренко, В.П.; Савчук, І.В.; Андреєв, І.В.; Беляєва, А.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Results of researches on decrease in the content of graphite’s inclusions in cemented carbides by introduction in cemented carbides mixes of additives which contain tungsten are presented.